Dark room disease - Dallas, D.; Sotiriadou, K.; Stavrakakis, P.; Chalaris, Michail; Sarafis, Pavlos (My University, 2010)
'Dark room' disease describes a collection of symptoms that some healthcare workers experience when exposed to film-processing chemicals. The purpose of this article is to examine the symptoms that are relevant to the use of these substances by radiology technicians (RT) and to investigate the practical precautions that should be taken by the employer and the radiographer in order to protect the radiographer from developing the 'dark room' disease.
Keywords: Dark room disease; Health effects; Industrial medicine; Prevention; Symptoms